2022
DOI: 10.1097/md.0000000000028475
|View full text |Cite
|
Sign up to set email alerts
|

Revision arthroplasty using a custom-made implant in the course of acetabular loosening of the J&J DePuy ASR replacement system - case report

Abstract: Rationale: Resurfacing arthroplasty using the J&J DePuy ASR system was withdrawn from surgical treatment due to the necessity of frequent revision procedures after its application. There have been many studies concerning treatment of acetabular bone loss using different operating techniques. However, we felt that data of custom - made implant usage in such cases is highly insufficient, and there is lack of evidence on its application in treatment of loosening of the previous implant. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a meta-analysis by Lee et al [ 9 ], MOM showed a higher revision rate than COC, possibly due to a lower wear rate of COC bearings and ceramic particles being more biocompatible than metallic. It is worth highlighting that in our case, the presence of bone defects primarily located around the medial acetabular wall in conjunction with a MOM articulation has the potential to exacerbate the development of a pseudotumor, which could negatively impact the overall results[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis by Lee et al [ 9 ], MOM showed a higher revision rate than COC, possibly due to a lower wear rate of COC bearings and ceramic particles being more biocompatible than metallic. It is worth highlighting that in our case, the presence of bone defects primarily located around the medial acetabular wall in conjunction with a MOM articulation has the potential to exacerbate the development of a pseudotumor, which could negatively impact the overall results[ 10 ].…”
Section: Discussionmentioning
confidence: 99%